Diffuse Large B-Cell Lymphoma 18 Years After Bilateral Lacrimal Gland IgG4-Related Disease: Case Report and Literature Review - Toshihiko Matsuo MD, PhD; Takehiro Tanaka MD, PhD; Kenji Notohara MD, PhD; Kazuya Okada MD, PhD (SAGE Publishing, 2022)
IgG4-related disease is a recently established clinical entity. The disease might serve as the background for later development of systemic lymphoma. This study aims to confirm the diagnosis of IgG4-related disease by re-staining lacrimal gland lesions diagnosed previously with low-grade lymphoma in a patient who developed systemic diffuse large B-cell lymphoma (DLBCL) 18 years later. A 53-year-old man developed bilateral lacrimal gland swelling and right submandibular gland swelling and was diagnosed by excision as low-grade lymphoma. In follow-up, positron emission tomography showed high uptake in the median hyoid 11 years later but no malignancy was detected by laryngeal submucosal biopsy. He was well with no treatment until 18 years later when he had palatal swelling and was diagnosed with DLBCL by oral floor biopsy. He had systemic lymphadenopathy, infiltration in paranasal sinuses, hypopharynx, small intestine, kidney, and prostate. He underwent 8 courses of R-CHOP and 3 courses of high-dose methotrexate and achieved complete remission with no relapse for 1 year thereafter. Re-immunostaining of paraffin blocks of bilateral lacrimal gland lesions showed IgG and IgG4-positive lymphocytes and plasma cells among lymphoid follicles separated by fibrous bundles, with 10 or more IgG4-positive cells in high-power field. The IgG4/IgG-positive cell ratio was 100% and the number of κ chain-positive cells and λ chain-positive cells was the same. The bilateral lacrimal lesions were thus re-diagnosed as IgG4-related disease. In conclusion, systemic DLBCL occurred approximately 20 years after lacrimal gland IgG4-related disease. Literature review revealed 12 patients with IgG4-related disease, including the present patient, who later developed lymphoma in the other organs.